Propofol or thiopentone as induction agents in romifidine-sedated and halothane-N2O-anesthetized dogs: a preliminary study. - Redondo, J I (2000)
The objective of this paper was to evaluate the use of romifidine as a premedicant in dogs before general anesthesia induced with propofol or thiopentone and maintained with halothane-N2O. Fifteen healthy dogs were anesthetized twice. Each dog received, as preanesthetic protocol, atropine (10 microg/kg, IM) and romifidine (40 microg/kg, IM); induction was delivered with propofol or thiopentone and anesthesia was maintained with halothane and N2O for 1 h. Some cardiovascular and respiratory variables and recovery times were recorded. Induction doses of propofol or thiopentone and the percentage of halothane necessary for maintaining anesthesia were also registered. Thiopentone as an induction agent is more respiratory depressive but is less hypotensive than propofol. Thiopentone reduces further the percentage of halothane necessary for maintaining the anesthesia. However, the quality of recovery is poorer, as the time to extubation is longer and the dogs occasionally had a violent recovery. The combination of romifidine, atropine, propofol, halothane, and N2O appears to be an effective combination for inducing and maintaining general anesthesia in healthy dogs.